The influence of morphological characteristics on throw speed in handball - Gardasevic, N.; Fulurija, D.; Joksimovic, M.; Eler, N.; Ahmedov, F. S. (International Journal of Physical Education, Fitness and Sports, 2020)
The diagnosis of morphological characteristics is an integral part of the entire training process in sports. This study aimed to determine the influence of morphological characteristics on the ball's speed of movement after the shoot from a spot and movement in handball. The sample included 36 female handball players aged 14.33 years. The predictor set consisted of 10 morphological variables. In comparison, the three variables constituted the criterion variables by which the ball's speed of movement was determined after different ways of shooting. Using regression analysis, it was found that the predictor set of variables explains about 70% of the variance for all three criterion variables. Individually, a statistically significant and positive influence on the speed of movement of the ball after the shot was recorded at the height and weight of the body, while a negative effect was observed for the variables; arm length, leg length and skin fold on the abdomen. Based on the results obtained, it can be concluded that morphological characteristics significantly influence the speed of movement of the ball after a shot in the handball, which can significantly contribute to the selection of handball players, as well as in establishing the tactics of handball, especially in situations where one shot decides the match. Also, the obtained results indicate the necessity of considering the age characteristics of the female respondents, that is, the need to adjust the training process to the period of intensive growth and development.